Left Ventricular Mechanical Dispersion and Its Value in Combination With Global Longitudinal Strain to Predict Reverse Remodeling in Patients With Heart Failure With Reduced Ejection Fraction - Fuyang Liu; Rui Li; Yujian Liu; Fei Ma; Hong Yang; Qiao Yang; Xiaofang Yang; Ting Yu; Hesong Zeng; Jiarong Tang; Hong Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Left ventricular mechanical dispersion (LV‐MD), an indicator of LV dyssynchrony, is not well studied in heart failure with reduced ejection fraction (HFrEF). This study aims to investigate the profile of LV‐MD in HFrEF, and evaluate whether it provides predictive information in terms of LV reverse remodeling (LVRR), particularly, on top of LV global longitudinal strain (LV‐GLS). Methods In this observational cohort study, 239 consecutive patients hospitalized for HFrEF from 2020 to 2022 were included, and baseline and follow‐up echocardiographic studies were performed. By strain analysis, LV‐MD was calculated as the SD of time to peak negative longitudinal strain from 17 LV segments. LVRR was defined as an increase in LVEF of ≥10% and a decrease in LV end‐diastolic diameter index of ≥10% or ≤33 mm/m2. Results During a median follow‐up of 19 months, LVRR occurred in 152 patients (64%). A great heterogeneity of LV‐MD ranging from 30 to 202 milliseconds was present in the cohort and 94 (84%) in 112 patients who were with LV‐MD >76 milliseconds had no left bundle‐branch block. LV‐MD ≤76 milliseconds independently predicted LVRR and possessed greater discriminatory ability than LV‐GLS by receiver operating characteristics analysis. Moreover, addition of LV‐MD ≤76 milliseconds and LV‐GLS ≤−5.5% to a multivariable model, including age, HF duration, systolic blood pressure, QRS duration and use of angiotensin receptor‐neprilysin inhibitors, improved predictive performance in terms of LVRR. Conclusions LV mechanical dyssynchrony is widely present in HFrEF, irrespective of left bundle‐branch block. LV‐MD is significantly associated with LVRR, independent of and superior to LV‐GLS. Combined assessments of LV‐MD and LV‐GLS provide additive value beyond clinical variables for predicting LVRR in HFrEF.